Pengaruh Pola Asuh Orang Tua dengan Perkembangan Kognitif Anak Usia Dini - Elva M. Sumirat; Safira Darmayanti; Juwita Moodumbi; Fitriyawati Ladiku (Inovasi Pendidikan dan Anak Usia Dini, 2025)
This study aims to analyze the influence of parenting styles on the cognitive development of early childhood children at KB AN-Nisa, South City District, Gorontalo City. The background of the study highlights that some children face difficulties in recognizing shapes, colors, and numbers, which are critical components of early cognitive development. A quantitative research approach was employed, utilizing observation and documentation techniques, involving a sample of 5 children out of a total of 35 students. The study explores how different parenting styles, including authoritarian, permissive, and democratic, impact the cognitive development of young children. The results demonstrate significant variations in cognitive abilities among children, influenced by the type of parenting they receive. Specifically, children raised in a responsive and supportive environment tend to show better cognitive development, particularly in areas such as shape and color recognition. These findings emphasize the crucial role of parenting style in providing cognitive stimulation for early childhood. They also highlight the importance of collaboration between parents and schools to optimize the cognitive development of young children, suggesting that a balanced, supportive approach to parenting can positively influence children’s learning outcomes. Therefore, this research contributes to understanding the connection between parenting and cognitive development in early childhood.